(untitled) (Zia e Tahqeeq, 2025)
A look at armed conflicts of ancient times reveals that only male members used to participate in such like conflicts and women and children used to be non-combatants and for the same reason, they were immune from any attack during these conflicts. However, with the passage of time, means and methods of warfare have been changed and women and children are also seen participating during armed conflicts, rather in some cases, women have become members of regular armed forces. Here a question arises, as to whether after taking part in conflicts, women and children lose their immunity? According to general principles of international humanitarian law (IHL), the answer can be given in affirmative to the extent of women, but to the extent of children, international law and domestic law of various countries, prohibit their participation in armed conflicts, below 18 years, and in some cases, below 16 years of age. So what would be the situation in case of participation of children in armed conflicts below 18 years of age? This paper is intended to find out answers of such like questions and suggest measures for their protection. General principles of Islamic law and IHL are almost the same, though there is some difference in detailed rules. Islamic law extends general protection to women and children during armed conflicts and provided detailed rules regarding their protection. But as long as women and children become combatants and participate during armed conflicts as active members, they lose their protection. These general principles are incorporated in the Holy Quran, Traditions of the Holy Prophet (SAW) and in the opinions of Orthodox Muslim jurists. However, in the light of modern armed conflicts, where war is fought through artificial intelligence and cyber networks, very little work has been done by Muslim scholars, as compared to IHL. So the primary object of this paper is to discuss the principles of Islamic law and IHL in light of modern armed conflicts and to highlight the parameters for the better protection of women and children.